Validity of a new weaning index of discontinuation from mechanical ventilation in intensive care unit - Eman Sabry Kamal; Gamal Abd Al- Rahman Salem; Ibrahim Aly Dwedar; Dalia Abd Elsattar El Embaby (Egyptian Journal of Chest Disease and Tuberculosis)
Background Failure to wean from mechanical ventilation (MV) is a frequent problem in the intensive care unit (ICU) setting. Herein, we investigate a new WI measured at the initial spontaneous breathing trial (SBT) in order to predict successful liberation from MV in mechanically ventilated ICU cases. Patients and methods This prospective cross-sectional study consisted of two phases; Phase I was designed to create a new WI from the criteria of 60 mechanically ventilated patients, while Phase II aimed to assess the accuracy of that index in another 40 patients. Results The incidence of failed weaning was 33.3% in phase I, and 35% in phase II. Multivariate regression analysis was done for phase I variables, and the following equation was created; (((Cough strength×0.743)–1.927)×0.05+((PaCO2 (mmHg)×-0.126)+6.786)×0.08+((mean airway pressure (CmH2O)×-1.304)+14.119)×0.193+((PaO2/FIO2 × 0.268)-58.555)×0.328+((rapid shallow breathing index×-0.485)+24.406)×0.353). Using a cut-off value of >0.69 and Applying this index in phase II, it showed a mean value of -1.43 and 4.67 in the failure and success groups, respectively (P<0.001). This new WI with cut-off value (>0.69) had 88.5% sensitivity, 57.1% specificity, and a 77.5% accuracy to predict the success of weaning from MV. Conclusion We developed a new WI using formula including (semiquantitative Cough strength, PCO2 gradient mean airway pressure, PO2/FIO2 ratio, Rapid shallow breathing index) with accepted sensitivity and moderate specificity for predicting successful weaning from MV in ICU patients. Its use should be encouraged in the ICU setting, especially by less experienced ICU physicians.